Implementation of Corporate Governance in Emerging Markets: Indonesia Stock Exchange and Singapore Stock Exchange - Sutejo, Bertha Silvia; Murhadi, Werner Ria; Octaviano, Fransisco (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The objective of this study is to examine the execution of corporate governance in manufacturing sector firms listed on Indonesia and Singapore's stock exchanges. The study reveals that an increase in the frequency of audit committee meetings has a substantial and favorable impact on Indonesia's financial performance. Conversely, in the case of Singapore, there is a notable adverse impact on financial performance. However, the presence of an independent board of commissioners, a higher frequency of commissioner’s meetings, a more significant percentage of managerial share ownership, and the magnitude of the Board of Commissioners have a substantial adverse impact on ROA. Conversely, the frequency of board commissioner meetings and the extent of managerial share ownership hurt Tobin's Q. The presence of an independent board of commissioners and the number of commissioners on the Board does not substantially impact Tobin's Q. In the case of Singapore, the presence of an independent board of commissioners, the size of the Board, the frequency of board meetings, and the overall percentage of managerial share ownership do not have a noteworthy impact on ROA. Conversely, the quantity of Board of Commissioners meetings has a favorable impact on Tobin's Q. The overall proportion of ownership held by managers negatively impacts Tobin's Q. Both the autonomy of the Board of Commissioners and its size do not substantially influence Tobin's Q.